OLYMPIC TEAM ROWER STROKE TECHNICAL ANALYSIS - Ciekurs, Kalvis; Krauksts, Viesturs; Krauksta, Daina; Grants, Juris; Smila, Baiba (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
It is much spoken about and researched how to increase the speed of moving in rowing. Many scientists have researched the technical aspects in rowing. Most part of researches is based on oxygen maximal consumption and other physiological changes during a load. Although there are various researches, stating the technical nuances of leg and arm work, comparatively little attention is paid to the role of the arm work. The cycle length in different distances and having different water flow – before the wind, against the wind and with the side wind is stated. The aim was to research one stroke technical nuances in rowing looking for stroke rate from 24 till 34. A pilot study was carried out. One Lithuanian Olympic team rower was participated this pilot study and he was tested in different stroke rate. The following methods were used in study: test exercise, video analysis with KinezioVideoAnalyzer 3.0. and mathematical statistics. The results: having stated the result average of stroke rate was 28,6 and speed of stroke was 0,82 sec. Conclusions: the obtained data from rower show small differences changing stroke rate.